On partial calmness for bilevel programming problem with a linear lower-level problem - D. E. Berezhnov; L. I. Minchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Numerous publications are devoted to bilevel programming problems. Despite a seemingly simple statement these problems are considerably difficult for numerical solving, and a significant part of research in the field of bilevel programming is devoted to identifying particular subsets of problems that allow for a numerical solution. One of such subsets consists of bilevel problems that possess the partial calmness property. Global partial calmness of bilevel programming problems with a linear lower-level problem is proven in this article.